MOSQUE AND REPRODUCTION OF ARAB IDENTITY IN THE HADRAMI COMMUNITY IN BETAWI - Syarif, Fajar; Ansor, Muhammad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
This research aims to analyze historical evidence of the usage of mosques by Arabs in old Jakarta to dominate society. This was shown through that they held a religious position in the mosques. Arabs have a strong influence on the diversity of society but they also try to influence and control the community. The main source used in this study is historical data. The data is interpreted by means of content analysis and using descriptive analytical method with qualitative approach. The conclusion of this research is that mosques are used by Arabs to reproduce Arabic identities.